Analisis Kesiapsiagaan Pemerintah dan Masyarakat Dalam Menghadapi Bencana Banjir di Wilayah Kampung Melayu Kota Jakarta Timur - Sasqia Fadhilah Atelia; Rahmat Hidayat; Mochamad Faizal Rizki (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to study and find out about the preparedness analysis of the government and the community in dealing with flood disasters in the Kampung Melayu area of East Jakarta City through Preparedness Parameters according to LIPI/UNESCO-ISDR 2006 in which there are five indicators which include, knowledge and attitudes, policies and guidelines, emergency response plans, disaster warnings and resource mobilization. This study uses a qualitative method with the determination of informants using purposive sampling technique. Data collection techniques were carried out through interviews, observations and documentation studies and then analyzed through three stages, namely data reduction, data presentation and conclusion drawing. The result of this research is that the community and government preparedness for flooding in Kampung Melayu in terms of knowledge and attitude dimensions is very minimal due to the lack of intellectual stimulus, then from the policy and guidance dimensions it is carried out through three stages, namely the pre-disaster stage, during the disaster and recovery, then the planning dimension. emergency response can work well in terms of making posts and providing tools needed by the community but not optimal in the evacuation and planning sector, the dimensions of disaster warning have gone well with the use of technology that can improve community preparedness and finally the dimension of resource mobilization is going well because people can ask for help preparedness in accordance with applicable procedures